ALIH USAHATANI PADI SAWAH KE TANAMAN JERUK NIPIS (Citrus auratifolia) DI DESA TRIDANA MULYA KECAMATAN LANDONO KABUPATEN KONAWE SELATAN - Kadek Yuli Sulistyani; Anas Nikoyan; Putu Arimbawa; Edi Syah Mihrad (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2024)
The objective of this study is to ascertain the underlying factors that precipitate the transition from wet-rice farming to lime farming, as well as to examine the impact of such farming conversions among farmers in Tridana Mulya Village. The study population was comprised of two groups: a group of 31 lime farmers and a group of seven rice farmers. The sampling technique employed was the census method, which entailed the inclusion of the entire population, resulting in a research sample of 38 individuals (31 lime farmers and 7 rice paddy farmers). Data were collected through the use of interview techniques, observation, and documentation of media sources in the form of questionnaires. The variables under investigation are the factors that influence the transfer of farming and the impact of such transfer. The data were analyzed using a descriptive method and an income formula. The results demonstrated that the factors that precipitated the transition from paddy rice farming to lime farming were attributable to a confluence of production, economic, and cultivation-related considerations. The production yield factor of lime farming has demonstrated an increase in production compared to paddy rice farming in Tridana Mulya Village. In terms of economic factors, lime farming has been shown to yield higher profits for farmers than paddy rice farming. Additionally, the cultivation factors associated with lime farming are considerably more straightforward, as the land only requires processing once, due to the fact that lime is a long-term crop, in contrast to paddy rice farming, which is dependent on seasonal conditions. The impact of switching farms includes both economic and environmental consequences. From an economic standpoint, farmers' income may change after switching from paddy rice farming to lime crops. This is because lime crops may yield higher profits than paddy rice, depending on various factors. From an environmental standpoint, the lack of use of chemical fertilizers or pesticides in lime farming may reduce the impact on the environment. This is in contrast to the opposite condition observed in paddy rice farming.